Application of encapsulated superabsorbent polymers in cementitious materials for stimulated autogenous healing. (18th September 2017) - Pelto, Jani; Leivo, Markku; Gruyaert, Elke; Debbaut, Brenda; Snoeck, Didier; De Belie, Nele
Abstract: Superabsorbent polymers have shown potential for use in mortar and concrete as self-healing agents. The main drawback is, however, that these superabsorbent polymers also absorb mixing water during the preparation and casting of mortar or concrete, leading to a loss in workability. To avoid the absorption of mixing water, superabsorbent polymers were coated using a fluid bed spraying process. The barrier coating consisted of three successive coating layers: polyvinylbutyral as primer/wetting layer, cyclo-olefin copolymer as a barrier layer and a sol–gel derived zirconium–silicon oxide as an adhesion-promoting topcoat layer. The coated SAPs were characterized, and their swelling determined to quantify the delay in uptake of water and Ca(OH)2 solution. The last was considered as the most important, as the SAPs will finally be applied in mortar or concrete having a pore solution with high pH. The results showed that swelling could be delayed to a large extent, but for a short time. Results showed that the self-sealing efficiency of mortars was not affected by coating the SAPs. Moreover, due to the reduced uptake of mixing water, the strength reduction, noticed when uncoated SAPs were added to the mortar, could partly be compensated.